Establishing a new model system for phase state measurments: The "swimming neuron" Paramecium - Paeger, Anne (Technische Universität Dortmund, 2022)
The origin of cellular excitability has not yet been clearly elucidated. It has been proposed that the nonlinear stimulus-response curve of excitable cells, manifesting in all-or-none pulses (action potentials), is based on a phase transition in the cell membrane and is not a purely molecule-based phenomenon. Indeed, typical traces of transitions have already been found in a small number of studies with excitable cells. Further investigations are needed to show whether these findings are of a general nature. In this work, state diagrams of the cell membrane of intact, motile specimens of the ”swimming neuron” Paramecium are measured. Therefore, individual cells were trapped in a microfluidic channel and investigated by fluorescence spectroscopy. The thermo-optical state diagrams exhibited reversible sigmoidal and break-like regimes, which are clear indications for a transition in the cell cortical membranes. This transition had a width of ∼ 10 − 15°C and a midpoint that was located ∼ 4°C below the growth temperature. It can be shifted due to changes in growth temperature or by the addition of an anesthetic (hexanol). These results suggested that the cortical membrane(s) of Paramecia reside in a phase transition regime under physiological growth conditions.

Der Ursprung zellulärer Erregbarkeit ist bis heute noch nicht eindeutig geklärt. Es wird vermutet, dass die nichtlineare Reiz-Antwort-Kurve erregbarer Zellen, die sich in Alles-oder-Nichts-Pulsen (Aktionspotentialen) manifestiert, auf einen Phasenübergang in der Zellmembran und nicht auf ein rein molekulares Phänomen zurückzuführen ist. Tatsächlich wurden bereits in wenigen Studien mit erregbaren Zellen typische Spuren von Übergängen gefunden. Ob diese Befunde allgemeiner Natur sind, müssen weitere Ergebnisse zeigen. In dieser Arbeit werden Zustandsdiagramme der Zellmembran intakter, beweglicher Exemplare des ”schwimmenden Neurons” Paramecium gemessen. Dazu wurden einzelne Zellen in einem mikrofluidischen Kanal eingefangen und fluoreszenzspektroskopisch untersucht. Die thermooptischen Zustandsdiagramme zeigten sigmoidale und bruchartige Regime, die klare Hinweise auf einen reversiblen Übergang in den kortikalen Zellmembranen sind. Dieser Übergang hatte eine Breite von ∼ 10 − 15°C und einen Mittelpunkt, der ∼ 4°C unterhalb der Wachstumstemperatur lag. Er kann aufgrund von Änderungen der Wachstumstemperatur oder durch Zugabe eines Anästhetikums (Hexanol) verschoben werden. Diese Ergebnisse legen nahe, dass sich die kortikale(n) Membran(en) von Paramecien unter physiologischen Wachstumsbedingungen im Bereich eines Phasenübergangs befinden.
Keywords: Paramecium; Fluorescence spectroscopy; Cortical membranes; Order transition; 530; Biomembran; Fluoreszenzspektroskopie